PubliCIDADE belle époque: a mídia impressa nos periódicos da cidade de Belém entre 1870-1912 - Santos, Luiz Cezar Silva dos (2010)
This thesis examines the relationships between advertising and urban living in the city of Belem, in the period known historically as belle epoque, between the years 1870 and 1912. From the analysis of advertising campaigns, the study focus on the construction of historical representations of the city of Belem of Para, and the evolution of advertising activity in this period. Reflecting on the representations constructed by the look of propaganda and publicity about the city of Belem, conveyed in advertisements for newspapers, almanacs and commemorative albums of the time, sought help to systematize the history of advertising activity between the late nineteenth century and early twentieth century in the Paris of the Tropics . Call belle epoque Amazon depicts the euphoria and the triumph of bourgeois society of the time over a period of effervescence economic, material and technological, from the extraction and marketing of rubber, a fact that has generated a cultural climate, intellectual and artistic which translated into new ways of think and live the life of the city of Belem. This study discusses between the years 1870 and 1912 the role and importance of advertising in this context